How to build a continental scale fireball camera network - Howie, R.; Paxman, J.; Bland, Phil; C Towner, M.; Cupak, M.; Sansom, E.; Devillepoix, H.A.R. (Springer Netherlands, 2017)
The expansion of the Australian Desert Fireball Network has been enabled by the development of a new digital fireball observatory based around a consumer digital camera. The observatories are more practical and much more cost effective than previous solutions whilst retaining high imaging performance. This was made possible through a flexible concurrent design approach, a careful focus on design for manufacture and assembly, and by considering installation and maintenance early in the design process. A new timing technique for long exposure fireball observatories was also developed to remove the need for a separate timing subsystem and data integration from multiple instruments. A liquid crystal shutter is used to modulate light transmittance during the long exposure which embeds a timecode into the fireball images for determining fireball arrival times and velocities. Using these observatories, the Desert Fireball Network has expanded to cover approximately 2.5 million square kilometres (around one third of Australia). The observatory and network design has been validated via the recovery of the Murrili Meteorite in South Australia through a systematic search at the end of 2015 and the calculation of a pre-atmospheric entry orbit. This article presents an overview of the design, implementation and performance of the new fireball observatories.